Guess what’s for dinner tonight? The role of packaged food and soft drinks in global obesity - Paz, Florencia; Díaz-Bonilla, Eugenio (International Food Policy Research Institute, 2020)
The percentage of population suffering from overweight or obesity is increasing worldwide, both in developed and developing countries, and for all subpopulations of age and gender (although data on the incidence of those problems seem to differ somewhat across sources of estimates. This paper attempts to shed some light on a specific debate: the role of consumption of different types of packaged foods and soft drinks on obesity trends. The paper is organized as follows. First, there is a discussion of other studies on drivers of obesity that can help to better frame the analysis in this paper. Second, we present the data utilized and the econometric approach utilized. Third, we present the results. A final section concludes.